Empirical Study on the Influencing Factors of Cultural Space Communication Effect in Lou Di City - Hong, Ye; Srijinda, Prakaikavin (Journal of Ecohumanism, 2024)
In the rapidly evolving media landscape, subcultural communication has attracted much attention. However, due to its long duration and low entertainment value, it struggles to create a lasting impact on collective and social memory. This research explores the potential of physical cultural spaces as a new avenue for effective cultural communication. Through quantitative research, the study focuses on the factors influencing the communication impact of public cultural spaces in Lou Di City. The results indicate that attributes such as attention-grabbing, engagement, innovation, ambiance, uniqueness, relevance, clarity, usefulness, recommendations, and satisfaction significantly influence the communication impact of cultural spaces. These findings can guide the enhancement and theoretical reconstruction of cultural spaces.